The extent to which the design of available reproductive health interventions fit the reproductive health needs of adolescents living in urban poor settings of Kisenyi, Kampala, Uganda - Doreen Tuhebwe; Susan Babirye; Steven Ssendagire; Freddie Ssengooba (BMC, 2021)
Abstract Background The rate at which informal urban settlements (slums) are developing in Low and Middle Income. Countries (LMICs) like Uganda is high. With this, comes the growing intersection between urbanization and the reproductive health of key populations. Currently, a number of interventions are being implemented to improve the Reproductive Health (RH) of adolescents in Kisenyi, the largest informal urban settlement in Kampala, the capital of Uganda. Despite these efforts, adolescent RH indicators have persistently remained poor in Kisenyi. This could be indicative of a gap between the provided and needed adolescent RH interventions. We assessed the fit between the available interventions and the RH needs of adolescents living in Kisenyi. Methods We conducted a qualitative study in July 2019-February 2020 in Kisenyi. The methodology was guided by the Word Health Organization global standards for quality-health care services for adolescents, the "For whom? Where? By whom? and What?" Framework of sexual RH service delivery and the realist evaluation approach. Eight focus group discussions were conducted with adolescents 15-19 years to explore their RH needs. The design and implementation of the available adolescent RH interventions were assessed by conducting Key Informant interviews with 10 RH service providers in Kisenyi. Validation meetings were held with adolescents and they scored the extent to which the various design features of the existing interventions fit the adolescents' RH needs. Results The available RH interventions focused on meeting the sexual RH needs like providing family planning services but less on social needs like livelihood and sanitation which the adolescents identified as equally important. While the providers designed intervention to target 10-24 year olds, the adolescents preferred to have interventions that specifically targeted the study population 15-19 years. Most interventions were facility-based while, the adolescents desired community based outreaches. Conclusion The packaging and mode of delivery of interventions were perceived less holistic to meet the adolescents' needs. Most interventions were designed to address the sexual and family planning needs while ignoring the wider social and livelihood needs. More holistic and outreach-based programming that addresses RH within the broader context of livelihood and sanitation requirements are more likely to be effective.